Apologizing in Daily Life: A Speech Act Analysis in English - Elisabeth Dwi Clara; Bernieke Anggita Ristia Damanik (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to analyze the forms and functions of apologizing as a speech act in everyday communication from a pragmatic and sociolinguistic perspective. Using a qualitative library research method, data were collected from recent scholarly sources and analyzed through the frameworks of speech act theory and politeness theory. The findings show that apologies are influenced by social factors such as power relations, social distance, and the severity of the offense. Apologies are often delivered indirectly, using hedges and softeners to mitigate face threats. This indicates that apologizing is not merely a personal expression of regret, but a strategic act to maintain social harmony.